2021
DOI: 10.3390/polym13213855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Pretreatments on Phosphorylation of Corypha umbraculifera L. Stem Pith Starch: A Comparative Study Using Dry-Heat, Heat-Moisture and Autoclave Treatments

Abstract: Talipot starch, a non-conventional starch source with a high yield (76%) from the stem pith of talipot palm (Corypha umbraculifera L.) was subjected to three different thermal treatments (dry-heat, heat-moisture and autoclave treatments) prior to phosphorylation. Upon dual modification of starch with thermal treatments and phosphorylation, the phosphorous content and degree of crosslinking significantly increased (p ≤ 0.05) and was confirmed by the increased peak intensity of P=O and P–O–C stretching vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
5
7
0
Order By: Relevance
“…[48] Moreover, all samples have higher elastic modulus than loss modulus, which indicates all samples had solid and elastic dominating gel structure than viscous. A similar study was reported for xanthan gum with DHT waxy rice starch and talipot crosslinked, talipot DHT starch by Li et al [65] and Aaliya et al [10]…”
Section: Steady Rheology and Dynamic Properties Of Starch Gelsupporting
confidence: 81%
See 4 more Smart Citations
“…[48] Moreover, all samples have higher elastic modulus than loss modulus, which indicates all samples had solid and elastic dominating gel structure than viscous. A similar study was reported for xanthan gum with DHT waxy rice starch and talipot crosslinked, talipot DHT starch by Li et al [65] and Aaliya et al [10]…”
Section: Steady Rheology and Dynamic Properties Of Starch Gelsupporting
confidence: 81%
“…In addition, the DHT increases the interactions between the starch chains and reduces the diffusions of amylopectin molecules, reducing the molecular interaction between water and starch. [56] A similar finding was reported by Aaliya et al [10] for crosslinked and dry-heated talipot starch. The swelling power of the OSA modified sample was the highest at all cooking temperatures, might be due to weakening of the intermolecular hydrogen bonds between bulky groups of OSA, which allowed more water molecules to interact with the free -OH groups of starch molecules.…”
Section: Swelling and Solubilitysupporting
confidence: 81%
See 3 more Smart Citations